Impact evaluation of research by the International Food Policy Research Institute on agricultural trade liberalization, developing countries, and WTO's Doha negotiations - International Food Policy Research Institute (International Food Policy Research Institute, 2009)
This study assesses the impact of IFPRI's work on the agriculture negotiations in the Doha Round of the World Trade Organization (WTO). It is set against the context of IFPRI's mission, which emphasizes food security and the interests of poor people in low-income countries and underlines the importance of active engagement in policy communications to link research to policy action.